ANALISIS KARAKTERISTIK MATERI PELAJARAN PENDIDIKAN AGAMA ISLAM DI JENJANG SD, SMP DAN SMA - Muh Haris Zubaidillah; M. Ahim Sulthan Nuruddaroini (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
Islamic Education subjects at various levels and types of education as a whole are in the scope of the Quran and Hadith, faith, morality, jurisprudence, and history. The scope of Islamic religious education includes the realization of harmony, harmony, and balance of human relations with Allah, self, fellow human beings, other creatures and the environment (Hablun Minallah wa hablun Minannas). So Islamic religious education is a conscious effort carried out by educators in order to prepare students to believe, understand, and practice Islamic teachings through the activities of guidance, teaching or training that has been determined to achieve the stated goals. In this study, we will discuss the analysis of the characteristics of Islamic Education materials at various levels and the type of education that aims to find out what the material is and where the advantages and disadvantages are. In this study it was found that PAI material at various levels and types of education, namely from kindergarten, elementary, junior high and high school had different characteristics, starting from the content of the material, material weight and depth of material also different from psychological, philosophical, sociological and technological aspects. Keywords: Characteristics, Material, Islamic Education, Elementary School, Middle School, High School